Systemic Candida Infections and Related Risk Factors in Newborns - Kurt, A. Nese Ctak; Kasar, Taner; Kurt, Abdullah; Benzer, Yaflar Dogan Derya; Aygun, A. Denizmen (Aves Yayincilik, Ibrahim Kara, 2008)
Aim: Systemic candida infections are the important causes of morbidity and mortality in the neonatal intensive care unit (NICU). In this study, the properties and risk factors of newborns affected by systemic candida infection in NICU are reported. Material and Method: Registration properties of fourteen patients diagnosed as having systemic candida infection were investigated retrospectively. Results: Mean birth weight was 1685 +/- 706 gram and mean gestational age was 32.9 +/- 4.4 weeks. Thirteen of the patients were premature, 11 had intubations, 9 had total parenteral nutrition and 12 had been given wide spectrum antibiotics for treatment of the infection. Conclusion: Similar to previous studies, prematurity was emphasized as the most common risk factor in this study also.
Keywords: Candida; risk factors; prematurity; wide spectrum antibiotic